Agronomic performance of maize hybrids for forage production in the 2019/2020 harvest - Garcia, Dionatas Alex; Pereira, José Luiz de Andrade Rezende; Garcia, Tássio Rezende; Souza, Vítor Marinello; Pereira Júnior, Luciano Luiz (Revista Agrogeoambiental, 2021)
Maize has great economic prominence in national and international agribusiness, being used for various purposes such as grain use and in the form of bulky (silage). This study aimed to evaluate the agronomic characteristics of twelve maize hybrids for silage production in Inconfidentes-MG. Twelve hybrids were used: 20A78PW, 2B512PW, 2B533PW, 2B688PW, 30F53LEPTERA, AG8740-PRO3, DKB345-PRO3, DKB363-PRO3, LG3055-PRO3, LG6036-PRO3, MAXIMUS-VIP3, and MG652PW. The treatments were implanted in a randomized block design (CBD) containing three repetitions. The experimental plots consisted of four lines of five meters in length and 0.8 m spacing between rows, with the two central lines as useful areas. The parameters evaluated were green matter productivity, dry matter productivity, plant height, ear height, average stalk thickness, cutting window, flowering, and cycle. The hybrids 20A78PW; 2B533PW; DKB345-PRO3, and DKB363-PRO3 presented the highest cut-off window values in relation to the others. LG3055-PRO3 hybrid presented the smallest cut-off window. The hybrids 30F53LEPTERA, AG8740, DKB345-PRO3, LG6036-PRO3, and MG652PW presented the highest plant height values. No statistical difference was observed between the hybrids for the variables: green matter productivity, ear height, and stalk thickness. Hybrids AG8740, DKB345-PRO3, LG6036-PRO3, and MG652PW obtained the highest dry matter productivity values. Hybrids 20A78PW, 2B533PW, DKB345-PRO3, and DKB363-PRO3 presented the lowest male and female flowering time. Hybrid DKB345-PRO3 stood out, showing great potential to be recommended and cultivated by silage producers.